2023
DOI: 10.1007/s00441-023-03770-w
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of dorsal root ganglia

Abstract: Dorsal root ganglia (DRG) contains thousands of sensory neurons that transmit information about our external and internal environment to the central nervous system. This includes signals related to proprioception, temperature, and nociception. Our understanding of DRG has increased tremendously over the last 50 years and has established the DRG as an active participant in peripheral processes. This includes interactions between neurons and non-neuronal cells such as satellite glia cells and macrophages that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…It is presumed that transcriptional changes in sensory ganglion non-neuronal cells could eventually lead to production of plethora of mediators. It has been shown that these mediators can sensitize sensory neurons (Ji et al, 2016;Donnelly et al, 2020;Gazerani, 2021) by direct communication with sensory neurons (Kim et al, 2016) and/or by regulating a plethora of neuronal channels, which could result in changing neuronal excitability and gating properties (Domoto et al, 2021;Haberberger et al, 2023;McGinnis and Ji, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is presumed that transcriptional changes in sensory ganglion non-neuronal cells could eventually lead to production of plethora of mediators. It has been shown that these mediators can sensitize sensory neurons (Ji et al, 2016;Donnelly et al, 2020;Gazerani, 2021) by direct communication with sensory neurons (Kim et al, 2016) and/or by regulating a plethora of neuronal channels, which could result in changing neuronal excitability and gating properties (Domoto et al, 2021;Haberberger et al, 2023;McGinnis and Ji, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports assigned critical roles in nociceptive signal transmission to dorsal root ganglion (DRG) glial (Huang et al, 2013;Donnelly et al, 2020;Gazerani, 2021;McGinnis and Ji, 2023) and immune cells, especially macrophages and neutrophils (Ji et al, 2016;Yu et al, 2020;Domoto et al, 2021;Lesnak et al, 2023). It is suggested that ganglion non-neuronal cells are capable of sensitizing neurons (Ji et al, 2016;Donnelly et al, 2020;Gazerani, 2021) by directly communicating with them and changing their gating properties (Domoto et al, 2021;Haberberger et al, 2023;McGinnis and Ji, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…200 The size of DRG also varies across species (in accordance with body size) as human DRG have approximately 4- to 5-fold more neurons per ganglion compared with the same ganglia in rodents. 85 In general, sensory neurons are concentrated near the DRG periphery while the center contains intersecting columns of nerve fibers, although this appearance can vary depending on the plane of section. 84,85 The numbers of sensory neurons may vary considerably in paired DRG for a given spinal cord segment.…”
Section: Comparative Neurobiology Of Gangliamentioning
confidence: 99%
“…85 In general, sensory neurons are concentrated near the DRG periphery while the center contains intersecting columns of nerve fibers, although this appearance can vary depending on the plane of section. 84,85 The numbers of sensory neurons may vary considerably in paired DRG for a given spinal cord segment. 246 Neurons in DRG range in size from 10 to over 100 µm in diameter (depending on age 172 and species), and neurons of all sizes are interspersed in the neuron-rich regions of sensory ganglia, with the bigger neurons frequently concentrated near the capsule.…”
Section: Comparative Neurobiology Of Gangliamentioning
confidence: 99%